CAPTURA DE CO2 DEVIDO À CARBONATAÇÃO DE MATERIAIS CIMENTÍCIOS: ABORDAGEM GERAL - Rigo, Eduardo; Possan, Edna; Mazurana, Lissandra (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In recent years, it has been discussed that cementitious materials, specially concrete, can capture CO2 due to carbonation, being able to compensate the cement production emissions, which is responsible for about 5% of global emissions of the gas. However, there are divergences in literature regarding the potential capture of CO2 due to carbonation. In this context, the study purpose is to make a panorama by compiling already published studies on CO2 uptake, indicating the main results found and identifying gaps in existing research. Researches was carried out in two bibliographic bases with main keywords of the subject, inserting filters. We found 22 relevant articles in the bases, which 10 were related to the experimental analyzes, 9 referring to calculation estimation through mathematical models or pre-existing data and 3 referring to "state of art " review. It was identified some frailties in calculation methodologies and the CO2 uptake potentials founded, and the future perspectives on CO2 capture context according to the papers. Therefore, the present study serves as a contribution to change cementitious materials concepts about sustainability and improve constructions life cycle analysis due to CO2 capture consideration.